O papel da FETRAF no aporte de políticas aos agricultores de base ecológica do município de Presidente Tancredo Neves-BA - Almeida, Vívian Libório de (2015)
The rural areas depends on the outcome of the interaction between men and natural resources and the problems arising from this relationship directly interfere in the performance of their productive activities. The subjects involved in promoting local development have to be vigilant and active in the search for ease impacts of the indiscriminate and uncontrolled action of man. The relationship historically constituted between man and the environment, where it is thought out separately productive aspects, it has resulted in negative effects with concern the environmental impacts, particularly for Family Agriculture. This form of thinking and acting in the field were quite encouraged by extension, derived from the diffusionist model offered by the state and public sector. This study presupposes the actions of the Federation of Workers in Family Agriculture in the State of Bahia (FETRAF - BA) that, since 2004, accompanying form, and articulates public policies for this social category aimed at its strengthening and consolidation. Thus, this proposal has the general objective of analyzing the contribution of FETRAF - BA as the interlocutor strategies for dealing with environmental issues from the perception of ecological farmers. The search for the analysis of the actions dialogue between the network performance of FETRAF-BA and Environmental Policy from the subject field, required the achievement of qualitative research with the use of semi-structured and participant observation. The methodology used in the research is part of a knowledge production process which implies an action marked by scientific dimensions and policy proposals made by a group of people, featuring a class action. The study enabled us to verify that the participation of FETRAF-BA was instrumental in the dialogue of Rural Public Policy and bringing practices and overcoming environmental problems strategies used by farmers in the development of productive activities. Moreover, this result supports the need to increase the reach strategies of representations of family farmers with policies aimed at strengthening this social category, but securing the use of natural resources in a sustainable way. Another aspect was explained despite the existing discussions on environmental issues, it was perceived remoteness of rural environmental policies of the subjects of the field and how these are built-in cross shapes, around sustainability and agroecology.